2017
DOI: 10.4067/s0718-95162017000400010
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting arbuscular mycorrhizal fungi of Chilean temperate rainforests

Abstract: While arbuscular mycorrhizal (AM) fungi in Chile have been widely documented in agro-ecosystems, there is a knowledge gap regarding AM fungal diversity in Chilean temperate rainforests. AM fungal communities of these forests are affected by several factors: the mountain systems of Chile (Coastal Range or Andes Mountains), the mycorrhizal dominance of the forest (either ectomycorrhizal -EM-or AM), soil chemistry, and altitude. We tested the effects of mountain system, mycorrhizal dominance, soil chemistry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…Samples from even lower elevation intact tundra meadows on Niwot Ridge (3500 m elevation) have shown over 80% colonization in some samples, which further supports this trend (Schmidt et al, 2008). This could be due to a lack of inoculum at high elevations (but see Marín et al, 2017 for increases with elevation), which could be a function of low plant density or a negative effect of cold temperature on AMF (Lugo et al, 2008;Yang et al, 2016). Since DSE are common in arctic and alpine environments, can tolerate cold temperatures (Mullen et al, 1998), and have been found in abundance at over 5250 m a.s.l.…”
Section: Plant and Environmental Predictors Of Colonization (H2)supporting
confidence: 54%
“…Samples from even lower elevation intact tundra meadows on Niwot Ridge (3500 m elevation) have shown over 80% colonization in some samples, which further supports this trend (Schmidt et al, 2008). This could be due to a lack of inoculum at high elevations (but see Marín et al, 2017 for increases with elevation), which could be a function of low plant density or a negative effect of cold temperature on AMF (Lugo et al, 2008;Yang et al, 2016). Since DSE are common in arctic and alpine environments, can tolerate cold temperatures (Mullen et al, 1998), and have been found in abundance at over 5250 m a.s.l.…”
Section: Plant and Environmental Predictors Of Colonization (H2)supporting
confidence: 54%
“…Root colonization rates of AMF have been shown to have no effect on AMF spore abundance or species richness in different studies (Aguilera et al 2017;Mafaziya and Madawala 2015;Marín et al 2017). Similarly, in our study, there was no relationship between AMF colonization rates and spore density (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Mycorrhizal interaction in Chilean ecosystems has focused on the study of arbuscular and ectomycorrhizal symbioses, contributing to the knowledge of functionality, distribution and presence in native flora, stress responses, and improvement of yield production of diverse agronomic species (Palfner 2001;Castillo et al 2006;Aguilera et al 2014;Aguilera et al 2015;Marín et al 2017). However, there are little studies analyzing the dynamic of mycorrhizal fungi in Chilean ecosystems, although recently, the number of published studies analyzing fungal associations, ecology, and germination of orchid seeds has increased (Table 1).…”
Section: The Chilean Orchidaceaementioning
confidence: 99%